Association between serum manganese and serum klotho in a 40–80-year-old American population from NHANES 2011–2016 - Guan, Guoyu; Cai, Jiasheng; Zheng, Songbai; Xiang, Yanzhen; Xia, Shijin; Zhang, Yixuan; Shi, Jiaqiang; Wang, Jun (Frontiers in Aging, 2023)
Objectives: Manganese is one of the essential trace elements that are required by the human body. Klotho protein is a classic anti-aging marker. The association between the levels of serum manganese and serum klotho in individuals between the ages of 40–80 in the United States remains unclear. Methods: Data for this cross-sectional study was obtained from the National Health and Nutrition Examination Survey (NHANES 2011–2016) in the United States. We performed multiple linear regression analyses to investigate the association between the levels of serum manganese and serum klotho. Furthermore, we performed a fitted smoothing curve according to a restricted cubic spline (RCS). Stratification and subgroup analyses were performed for further verification of the results. Results: Weighted multivariate linear regression analysis showed that serum manganese levels were independently and positively associated with serum klotho levels (β = 6.30, 95% confidence interval: 3.30–9.40). Kruskal–Wallis test showed that participants with higher manganese quartiles had higher serum klotho levels (Q1: 808.54 ±256.39 pg/mL; Q2: 854.56 ±266.13 pg/mL; Q3: 865.13 ±300.60 pg/mL; and Q4: 871.72 ±338.85pg/mL, P < 0.001). The RCS curve indicated that the association between the levels of serum manganese and serum klotho was nonlinear. Furthermore, a significantly positive association was found between serum manganese and serum klotho levels in the majority of subgroups. Conclusions: A nonlinear and positive association was found between the levels of serum manganese and serum klotho in individuals aged 40–80 in the United States according to the NHANES (2011–2016).